2016
DOI: 10.1007/s00334-016-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Indus crop processing: combining phytolith and macrobotanical analyses to consider the organisation of agriculture in northwest India c. 3200–1500 bc

Abstract: This paper presents a preliminary study combining macrobotanical and phytolith analyses to explore crop processing at archaeological sites in Haryana and Rajasthan, northwest India. Current understanding of the agricultural strategies in use by populations associated with South Asia's Indus Civilisation (3200-1900 BC) has been derived from a small number of systematic macrobotanical studies focusing on a small number of sites, with little use of multi-proxy analysis. In this study both phytolith and macrobotan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…Here, we will focus on cereals, as they are the most commonly reported botanical remains from Indus sites (Fuller and Madella 2002;Bates 2016, forthcoming). Cereals were also the most dense, the most ubiquitous and proportionately the largest plant group from the quantified sites that have been explored (Bates 2016;Bates et al 2017aBates et al , 2017bPetrie and Bates in press;Petrie et al 2016Petrie et al , 2017. Even when focusing just on the cereals, there are difficulties in making comparisons, as each species has different rates of production.…”
Section: Quantifying Archaeobotanical Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will focus on cereals, as they are the most commonly reported botanical remains from Indus sites (Fuller and Madella 2002;Bates 2016, forthcoming). Cereals were also the most dense, the most ubiquitous and proportionately the largest plant group from the quantified sites that have been explored (Bates 2016;Bates et al 2017aBates et al , 2017bPetrie and Bates in press;Petrie et al 2016Petrie et al , 2017. Even when focusing just on the cereals, there are difficulties in making comparisons, as each species has different rates of production.…”
Section: Quantifying Archaeobotanical Datasetsmentioning
confidence: 99%
“…A different pattern has been Electronic supplementary material The online version of this article (doi:10.1007/s12520-017-0489-2) contains supplementary material, which is available to authorized users. observed in several new archaeobotanical datasets from the north-east zone of the Indus Civilisation, however (Bates 2016;Bates et al 2017aBates et al , 2017bPetrie and Bates in press;Petrie et al 2016Petrie et al , 2017. Analysis of floated samples from five of the six small village sites excavated by the Land, Water and Settlement project (Singh et al 2008(Singh et al , 2010a(Singh et al , 2010b(Singh et al , 2011(Singh et al , 2013a(Singh et al , 2013bPetrie et al 2009Petrie et al , 2016Petrie et al , 2017Pawar 2012;Bates 2016;Bates et al 2017aBates et al , 2017bParikh and Petrie 2017) that are spread across the plains of north-west India has suggested that despite there being some similarities (such as the range of taxa cultivated), there were differences in the proportions of individual crops at each settlement and in each period (Bates 2016;Bates et al 2017aBates et al , 2017bPetrie et al 2016Petrie et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of these data is further complicated by plant morphology, particularly the fact that while Panicum sp. millet produces many more seeds per head than either wheat or barley, millet seeds are smaller and less calorific per grain (Bates et al 2017b). Therefore, while summer crops were present at Harappa throughout the sequence, it is arguable that the preserved quantities of seeds indicate that they were a relatively minor component of the overall crop assemblage, particularly in contrast to the exploitation of wheat and barley.…”
Section: Harappamentioning
confidence: 95%
“…During the PGW period, crop proportions suggest that mixed intercropping of millet was predominant in the summer season, but that the overarching strategy involved sequential multi-cropping when the winter season crops are taken into consideration. It is notable, however, that no macro remains of winter weeds were attested, despite the phytolith evidence suggesting their presence (Bates 2016, Bates et al 2017b). Exploitation of pulses and fruits at PGW period Burj was even more limited than at Dabli vas Chugta.…”
Section: Burjmentioning
confidence: 99%
See 1 more Smart Citation